Early prediction of pediatric acute kidney injury from the emergency department: A pilot study - Hanson, Holly R.; Carlisle, Michael A.; Bensman, Rachel S.; Byczkowski, Terri; Depinet, Holly; Terrell, Tara C.; Pitner, Hilary; Knox, Ryan; Goldstein, Stuart L.; Basu, Rajit K. (The American journal of emergency medicine, 2021)
Identifying acute kidney injury (AKI) early can inform medical decisions key to mitigation of injury. An AKI risk stratification tool, the renal angina index (RAI), has proven better than creatinine changes alone at predicting AKI in critically ill children. To derive and test performance of an “acute” RAI (aRAI) in the Emergency Department (ED) for prediction of inpatient AKI and to evaluate the added yield of urinary AKI biomarkers. Study of pediatric ED patients with sepsis admitted and followed for 72 h. The primary outcome was inpatient AKI defined by a creatinine >1.5× baseline, 24–72 h after admission. Patients were denoted renal angina positive (RA+) for an aRAI score above a population derived cut-off. Test characteristics evaluated predictive performance of the aRAI compared to changes in creatinine and incorporation of 4 urinary biomarkers in the context of renal angina were assessed. 118 eligible subjects were enrolled. Mean age was 7.8 ± 6.4 years, 16% required intensive care admission. In the ED, 27% had a +RAI (22% had a >50% creatinine increase). The aRAI had an AUC of 0.92 (0.86–0.98) for prediction of inpatient AKI. For AKI prediction, RA+ demonstrated a sensitivity of 94% (69–99) and a negative predictive value of 99% (92–100) (versus sensitivity 59% (33–82) and NPV 93% (89–96) for creatinine ≥2× baseline). Biomarker analysis revealed a higher AUC for aRAI alone than any individual biomarker. This pilot study finds the aRAI to be a sensitive ED-based tool for ruling out the development of in-hospital AKI.